DAMPAK TRANSFORMASI OJEK ONLINE TERHADAP OJEK KONVENSIONAL (STUDI KASUS DI STASIUN JEMBER) - Halimatuz Zahro; Sri Devi Januarifka Fitria, Yuan Amukti Palupi (CV. ADIBA AISHA AMIRA, 2023)
Gojek and Grab are companies engaged in the transportation sector that use scientific and technological sophistication that can be downloaded via mobile phones. The emergence of online motorcycle taxis is one of the major influences on the disadvantages of conventional motorcycle taxis. However, with the progress of the times as it is today, many people are downloading the gojek and grab applications, this is happening due to the rise of online motorcycle taxis and people are more interested in using them. As hapened at Jember Station, in front of the exit there is a conventional motorcycle taxi stand ready to pick up and drop off, but most passengers there prefer to use online motorcycle taxis. This research is a type of qualitative research, where the result of the data are obtained through filed observations, interviews, and documentation in the form of pictures and sound recordings. In this study using a phenomenological approach, where the approach knows in detail and in detail about the actions and experiences of individuals there. The informants involved were three people, with the criteria of a conventional motorcycle taxi driver taking a stop at Jember Station